Teachers' Directive Speech Acts to Motivate Junior High School Students in Indonesian Language Subjects after the Covid-19 Pandemic Online Classes - Iswatiningsih, Daroe; Fauzan; Diana, Purwati Zisca; Winarsih, Anis Dwi; Marwiah (Kembara: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya (Online), 2023)
Speech acts motivate teachers to make students more excited, active, diligent, and learn more. Directive speech acts motivate speech that invites students to do something as the teacher hopes to do according to the goal. This study aims to describe (1) the form of motivating directive speech acts in Indonesian learning in the classroom, (2) directive speech act strategies motivate teachers to students and (3) student responses to motivating directive speech acts in Indonesian learning in the classroom. This type of research is qualitative. The research data is in the form of directive speech motivating teachers, motivating directive speech strategies, and student response speech. Data source from seven learning videos Indonesian junior high school level on YoTube covid 19 pandemic. Data collection techniques use documentation, listen, and record. Data analysis techniques use interactive analysis with stages of data reduction, data presentation, and drawing of inference/ verification. The results of the study consisted of three things, namely (1) the form of directive speech act motivating teachers in students stated a) expectations, b) goals, c) ensure, d) reminded, e) imposed, f) solicitations, and h) praise; (2) directive speech action strategies motivate teachers to learners to be implemented in a direct way; and (3) students' responses to directive speech acts are motivated in the form of words of approval and action. The contribution of this research to learning is that teachers can take advantage of language that has the power to move students to be excited and actively learn.